Water-based conductive binder for lithium ion battery and preparation method of water-based conductive binder
The aqueous conductive adhesive prepared by emulsion polymerization technology uses modified conductive materials and conductive polymers to form a three-dimensional conductive network, and introduces self-healing and thermal response functions, solving the environmentally friendly and high performance of traditional adhesives. The lack of this paper significantly improves the conductivity and cycle stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202411805214.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional lithium-ion battery adhesives have shortcomings in terms of environmental friendliness and high performance, and they are prone to failure of bonding due to changes in electrode volume during circulation, affecting battery performance and life.
An aqueous conductive adhesive is prepared by emulsion polymerization technology, which consists of modified conductive carbon black, modified carbon nanotubes, modified graphene, conductive polymer and functional enhancer to form a stable three-dimensional conductive network and introduce self-healing and thermal response functions.
It significantly improves the conductivity and cyclic stability of the adhesive, reduces interface resistance, improves the rate performance and energy density of the battery, and avoids the pollution of the environment by organic solvents, and enhances the environmental friendliness of the material.
Smart Images

Figure CN119463750A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of binders, and in particular to a water-based conductive binder for lithium-ion batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronics, energy storage devices and electric vehicles due to their advantages such as high energy density, long cycle life and environmental friendliness. Electrode binder is one of the key materials in the preparation of lithium-ion battery electrodes. Its function is to tightly bond the active material, conductive agent and current collector and maintain the stability of the electrode structure. However, traditional binders (such as PVDF) mostly use organic solvents as dispersion media, which are not environmentally friendly and cannot meet the requirements of high-performance batteries for comprehensive properties such as conductivity, flexibility, bonding strength and chemical corrosion resistance. In addition, existing binders are prone to bonding failure due to changes in electrode volume during the cycle process, which in turn affects battery performance and life. Therefore, the development of new water-based conductive binders, especially material systems with excellent conductivity, environmental protection and multifunctional enhanced properties, is an important direction for the development of lithium-ion battery technology.
[0003] In recent years, with the development of functional polymers, modified conductive materials and green chemical technology, water-based conductive binders prepared by emulsion polymerization have shown good application prospects. By rationally designing the compounding of modified conductive agents and functional enhancers, the electrode binder can be balanced and optimized in terms of conductivity, mechanical strength, flexibility and environmental protection. However, there is still a lack of a water-based binder that has high conductivity, environmental friendliness and multifunctional properties on the market. Therefore, in response to this pain point, the present invention proposes a water-based conductive binder for lithium-ion batteries that combines high-performance conductivity, multifunctional enhancement and green environmental protection. Summary of the invention
[0004] The object of the present invention is to provide a water-based conductive binder for lithium-ion batteries and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a water-based conductive binder for lithium-ion batteries, wherein the conductive binder is an in-situ reaction complex of an emulsion polymer and a conductive material, and comprises the following components in parts by weight: 1 to 10 parts of a surfactant, 5 to 40 parts of acrylic acid and its salts, 5 to 40 parts of acrylic esters and their derivatives, 0.1 to 2 parts of an initiator, 1 to 15 parts of a modified conductive agent, 0.5 to 5 parts of a conductive polymer, 2 to 15 parts of a functional enhancer, 1 to 5 parts of an environmentally friendly additive, and 50 to 200 parts of deionized water.
[0006] Preferably, the conductive adhesive is an in-situ reaction complex of an emulsion polymer and a conductive material, comprising the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic esters and their derivatives, 1.5 parts of an initiator, 12 parts of a modified conductive agent, 3 parts of a conductive polymer, 8 parts of a functional enhancer, 2.5 parts of an environmentally friendly additive, and 200 parts of deionized water.
[0007] Preferably, the modified conductive agent is any one of modified conductive carbon black, modified carbon nanotubes, and modified graphene, and the modification steps are as follows:
[0008] Modified conductive carbon black: suspend the conductive carbon black in water, add nitric acid / sulfuric acid mixed acid with a volume ratio of 1:3, disperse by ultrasonic for 1 hour, and stir at 80°C for 4 hours;
[0009] Modified carbon nanotubes: disperse carbon nanotubes in nitric acid solution, stir and react at 80°C for 5 hours to introduce carboxyl functional groups, then react with ammonia water to generate amino carbon nanotubes, and finally graft polymerize with acrylic monomers through amino groups;
[0010] Modified graphene: Graphene oxide is used as a precursor, and a hydrothermal method is used to reduce and generate partially reduced graphene oxide. Pyrrole or aniline monomers are modified on the surface of graphene oxide, and a conductive polymer composite is formed through in-situ chemical oxidation polymerization.
[0011] Preferably, the conductive polymer is any one of polypyrrole or polyaniline.
[0012] Preferably, the functional enhancer includes 2 parts of self-healing monomer, 2 parts of thermal responsive monomer, 1 part of ceramic nanoparticles, and 3 parts of interface coupling agent; wherein the self-healing polymer is urethane acrylate; the thermal responsive monomer is N-isopropylacrylamide; the ceramic nanoparticles are any one of TiO2, Al2O3, and SiO2; and the interface coupling agent is any one of silane coupling agent and titanate coupling agent.
[0013] Preferably, the environmentally friendly additive comprises 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is any one of carboxymethyl starch, carboxymethyl cellulose, and hydroxypropyl cellulose; and the biodegradable plasticizer is polyadipate.
[0014] Preferably, the surfactant is selected from any one or more of the following combinations: sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium pyrophosphate, polyethylene glycol ether, polypropylene glycol ether, ethylene oxide-propylene oxide block copolymer, polyvinyl alcohol, polysorbate, and sorbitan fatty acid ester.
[0015] Preferably, the acrylic acid and its salts include any one or more combinations of acrylic acid, methacrylic acid and its sodium, potassium, lithium, ammonium salts, itaconic acid and its salts, maleic acid and its salts; the acrylic acid ester and its derivatives include any one or more combinations of methyl acrylate, ethyl acrylate, propyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, polyethylene glycol acrylate, etc.
[0016] Preferably, the initiator includes any one or more combinations of potassium persulfate, ammonium persulfate, and azobisisobutylamidine hydrochloride.
[0017] The present invention also discloses a method for preparing a water-based conductive binder for lithium-ion batteries, comprising the following steps:
[0018] Add a surfactant to deionized water, stir evenly, then add a modified conductive agent, and perform ultrasonic dispersion for 30 to 60 minutes at room temperature to evenly disperse the modified conductive agent in water to obtain a dispersion D;
[0019] Acrylic acid and its salts and part of acrylic acid esters and their derivatives are sequentially added to the dispersion D, and an initiator is added. After nitrogen is passed through to deoxygenate for 10 to 30 minutes, the system is heated to 60 to 85° C. and stirred at a constant temperature for 1 to 4 hours to form a pre-reactant A.
[0020] A portion of the pre-reactant A is mixed with the remaining acrylate and its derivatives, and a conductive polymer and a functional enhancer are added, and emulsified and stirred at room temperature for 30 minutes to obtain an emulsified monomer B. Meanwhile, the remaining initiator is dissolved in deionized water to obtain an initiator solution C;
[0021] The emulsified monomer B and the initiator solution C are slowly added to the remaining pre-reactant A by dropwise addition (2 to 10 hours), and the temperature of the reaction system is maintained at 65 to 85°C. After the dropwise addition is completed, the reaction is carried out at a constant temperature for 2 to 8 hours to ensure that the polymerization is fully completed to form a uniform adhesive matrix;
[0022] Add environmentally friendly additives to the adhesive matrix, stir evenly, filter and remove impurities, cool to room temperature, and obtain a finished adhesive.
[0023] Technical effects and advantages of the present invention:
[0024] 1. The present invention uses modified conductive carbon black, modified carbon nanotubes and modified graphene as conductive agents, and combines them with conductive polymers to form a stable three-dimensional conductive network in the binder, which significantly improves the conductive properties of the binder. This network structure helps to reduce interface resistance and improve the rate performance and energy density of the battery;
[0025] 2. In the present invention, by introducing the functional enhancers of self-healing monomers, thermal responsive monomers, ceramic nanoparticles, and interface coupling agents, the binder has higher tensile and crack resistance and can maintain a good bonding effect when the electrode volume changes. At the same time, the self-healing function can extend the service life of the binder, thereby improving the cycle stability of the battery;
[0026] 3. The present invention uses water as a dispersion medium, which completely avoids the environmental pollution caused by organic solvents used in traditional binders. In addition, the addition of environmentally friendly additives such as bio-based materials and biodegradable plasticizers further improves the environmental friendliness of the material and makes the treatment of waste batteries safer;
[0027] 4. The present invention adopts emulsion polymerization technology, and through multi-step pre-reaction and step-by-step polymerization process, ensures the uniform distribution of binder components and the controllability of molecular structure, while reducing energy consumption in the preparation process. The water-based conductive binder can be adapted to a variety of positive and negative electrode materials (such as silicon-based negative electrode, high-nickel ternary positive electrode, etc.), meet the needs of different lithium-ion battery application scenarios, and show excellent interface compatibility and adhesion properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a schematic diagram of the preparation process of a water-based conductive adhesive for lithium-ion batteries. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive being an in-situ reaction complex of an emulsion polymer and a conductive material, comprising the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a modified conductive agent, 3 parts of a conductive polymer, 8 parts of a functional enhancer, 2.5 parts of an environmentally friendly additive, and 200 parts of deionized water.
[0032] The modified conductive agent is modified conductive carbon black, and the modification steps are as follows;
[0033] Modified conductive carbon black: suspend the conductive carbon black in water, add nitric acid / sulfuric acid mixed acid with a volume ratio of 1:3, disperse by ultrasonic for 1 hour, and stir at 80°C for 4 hours;
[0034] The conductive polymer is polypyrrole.
[0035] The functional enhancer includes 2 parts of self-healing monomer, 2 parts of thermal response monomer, 1 part of ceramic nanoparticles, and 3 parts of interface coupling agent; wherein, the self-healing polymer is urethane acrylate; the thermal response monomer is N-isopropyl acrylamide; the ceramic nanoparticles are TiO2; and the interface coupling agent is a silane coupling agent.
[0036] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is carboxymethyl starch; and the biodegradable plasticizer is polyadipate.
[0037] The surfactant is selected from sodium lauryl sulfate.
[0038] Acrylic acid and its salts are methacrylic acid and its salts; acrylic acid esters and their derivatives include methyl acrylate.
[0039] The initiator is potassium persulfate.
[0040] The preparation method is:
[0041] Add a surfactant to deionized water, stir evenly, then add a modified conductive agent, and perform ultrasonic dispersion for 50 minutes at room temperature to evenly disperse the modified conductive agent in water to obtain a dispersion D;
[0042] Acrylic acid and its salts and part of acrylic acid esters and their derivatives are sequentially added to the dispersion D, and an initiator is added. After nitrogen is passed through to deoxygenate for 20 minutes, the system is heated to 85° C. and stirred at a constant temperature for 3 hours to form a pre-reactant A.
[0043] A portion of the pre-reactant A is mixed with the remaining acrylate and its derivatives, and a conductive polymer and a functional enhancer are added, and emulsified and stirred at room temperature for 30 minutes to obtain an emulsified monomer B. Meanwhile, the remaining initiator is dissolved in deionized water to obtain an initiator solution C;
[0044] The emulsified monomer B and the initiator solution C are slowly added to the remaining pre-reactant A by dropwise addition (2 to 10 hours), and the temperature of the reaction system is maintained at 80°C. After the dropwise addition is completed, the reaction is carried out at a constant temperature for 6 hours to ensure that the polymerization is fully completed to form a uniform adhesive matrix;
[0045] Add environmentally friendly additives to the adhesive matrix, stir evenly, filter and remove impurities, cool to room temperature, and obtain a finished adhesive.
[0046] Example 2
[0047] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive being an in-situ reaction complex of an emulsion polymer and a conductive material, comprising the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a modified conductive agent, 3 parts of a conductive polymer, 8 parts of a functional enhancer, 2.5 parts of an environmentally friendly additive, and 200 parts of deionized water.
[0048] The modified conductive agent is modified carbon nanotubes, and the modification steps are as follows;
[0049] Modified carbon nanotubes: disperse carbon nanotubes in nitric acid solution, stir and react at 80°C for 5 hours to introduce carboxyl functional groups, then react with ammonia water to generate amino carbon nanotubes, and finally graft polymerize with acrylic monomers through amino groups;
[0050] The conductive polymer is polyaniline.
[0051] The functional enhancer includes 2 parts of self-healing monomer, 2 parts of thermal response monomer, 1 part of ceramic nanoparticles, and 3 parts of interface coupling agent; wherein, the self-healing polymer is urethane acrylate; the thermal response monomer is N-isopropyl acrylamide; the ceramic nanoparticles are Al2O3; and the interface coupling agent is a silane coupling agent.
[0052] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is carboxymethyl cellulose; and the biodegradable plasticizer is polyadipate.
[0053] The surfactant is selected from polysorbates.
[0054] Acrylic acid and its salts are methacrylic acid and its salts; acrylate and its derivatives are hydroxyethyl acrylate.
[0055] The initiator is ammonium persulfate.
[0056] The preparation method is the same as that of Example 1.
[0057] Example 3
[0058] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive being an in-situ reaction complex of an emulsion polymer and a conductive material, comprising the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a modified conductive agent, 3 parts of a conductive polymer, 8 parts of a functional enhancer, 2.5 parts of an environmentally friendly additive, and 200 parts of deionized water.
[0059] The modified conductive agent is modified graphene, and the modification steps are as follows;
[0060] Modified graphene: Graphene oxide is used as a precursor, and a hydrothermal method is used to reduce and generate partially reduced graphene oxide. Pyrrole or aniline monomers are modified on the surface of graphene oxide, and a conductive polymer composite is formed through in-situ chemical oxidation polymerization.
[0061] The conductive polymer is polypyrrole.
[0062] The functional enhancer includes 2 parts of self-healing monomer, 2 parts of thermal response monomer, 1 part of ceramic nanoparticles, and 3 parts of interface coupling agent; wherein, the self-healing polymer is urethane acrylate; the thermal response monomer is N-isopropyl acrylamide; the ceramic nanoparticles are SiO2; and the interface coupling agent is titanate coupling agent.
[0063] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is hydroxypropyl cellulose; and the biodegradable plasticizer is polyadipate.
[0064] The surfactant is selected from sodium dodecylbenzene sulfonate.
[0065] Acrylic acid and its salts are methacrylic acid and its salts; acrylic acid ester and its derivatives are methyl methacrylate.
[0066] The initiator is azobisisobutyramidine hydrochloride.
[0067] The preparation method is the same as that of Example 1.
[0068] Comparative Example 1
[0069] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive is an in-situ reaction complex of an emulsion polymer and a conductive material, and comprises the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a conductive agent, 8 parts of a functional enhancer, 2.5 parts of an environmental protection additive, and 200 parts of deionized water.
[0070] The conductive agent is conductive carbon black.
[0071] The functional enhancer includes 2 parts of self-healing monomer, 2 parts of thermal response monomer, 1 part of ceramic nanoparticles, and 3 parts of interface coupling agent; wherein, the self-healing polymer is urethane acrylate; the thermal response monomer is N-isopropyl acrylamide; the ceramic nanoparticles are TiO2; and the interface coupling agent is a silane coupling agent.
[0072] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is carboxymethyl starch; and the biodegradable plasticizer is polyadipate.
[0073] The surfactant is selected from sodium lauryl sulfate.
[0074] Acrylic acid and its salts are methacrylic acid and its salts; acrylic acid esters and their derivatives include methyl acrylate.
[0075] The initiator is potassium persulfate.
[0076] The preparation method is the same as that of Example 1.
[0077] Comparative Example 2
[0078] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive is an in-situ reaction complex of an emulsion polymer and a conductive material, and comprises the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a conductive agent, 8 parts of a functional enhancer, 2.5 parts of an environmental protection additive, and 200 parts of deionized water.
[0079] The conductive agent is carbon nanotubes.
[0080] The functional enhancer includes 2 parts of self-healing monomer, 2 parts of thermal response monomer, 1 part of ceramic nanoparticles, and 3 parts of interface coupling agent; wherein, the self-healing polymer is urethane acrylate; the thermal response monomer is N-isopropyl acrylamide; the ceramic nanoparticles are TiO2; and the interface coupling agent is a silane coupling agent.
[0081] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is carboxymethyl starch; and the biodegradable plasticizer is polyadipate.
[0082] The surfactant is selected from sodium lauryl sulfate.
[0083] Acrylic acid and its salts are methacrylic acid and its salts; acrylic acid esters and their derivatives include methyl acrylate.
[0084] The initiator is potassium persulfate.
[0085] The preparation method is the same as that of Example 1.
[0086] Comparative Example 3
[0087] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive is an in-situ reaction complex of an emulsion polymer and a conductive material, and comprises the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a conductive agent, 8 parts of a functional enhancer, 2.5 parts of an environmental protection additive, and 200 parts of deionized water.
[0088] The conductive agent is graphene.
[0089] The functional enhancer includes 2 parts of self-healing monomer, 2 parts of thermal response monomer, 1 part of ceramic nanoparticles, and 3 parts of interface coupling agent; wherein, the self-healing polymer is urethane acrylate; the thermal response monomer is N-isopropyl acrylamide; the ceramic nanoparticles are TiO2; and the interface coupling agent is a silane coupling agent.
[0090] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is carboxymethyl starch; and the biodegradable plasticizer is polyadipate.
[0091] The surfactant is selected from sodium lauryl sulfate.
[0092] Acrylic acid and its salts are methacrylic acid and its salts; acrylic acid esters and their derivatives include methyl acrylate.
[0093] The initiator is potassium persulfate.
[0094] The preparation method is the same as that of Example 1.
[0095] Comparative Example 4
[0096] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive being an in-situ reaction complex of an emulsion polymer and a conductive material, comprising the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a conductive agent, 3 parts of a conductive polymer, 2.5 parts of an environmentally friendly additive, and 200 parts of deionized water.
[0097] The conductive agent is conductive carbon black.
[0098] The conductive polymer is polypyrrole.
[0099] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is carboxymethyl starch; and the biodegradable plasticizer is polyadipate.
[0100] The surfactant is selected from sodium lauryl sulfate.
[0101] Acrylic acid and its salts are methacrylic acid and its salts; acrylic acid esters and their derivatives include methyl acrylate.
[0102] The initiator is potassium persulfate.
[0103] The preparation method is the same as that of Example 1.
[0104] Comparative Example 5
[0105] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive being an in-situ reaction complex of an emulsion polymer and a conductive material, comprising the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a conductive agent, 3 parts of a conductive polymer, 2.5 parts of an environmentally friendly additive, and 200 parts of deionized water.
[0106] The conductive agent is carbon nanotubes.
[0107] The conductive polymer is polypyrrole.
[0108] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is carboxymethyl starch; and the biodegradable plasticizer is polyadipate.
[0109] The surfactant is selected from sodium lauryl sulfate.
[0110] Acrylic acid and its salts are methacrylic acid and its salts; acrylic acid esters and their derivatives include methyl acrylate.
[0111] The initiator is potassium persulfate.
[0112] The preparation method is the same as that of Example 1.
[0113] Comparative Example 6
[0114] A water-based conductive adhesive for lithium-ion batteries, the conductive adhesive being an in-situ reaction complex of an emulsion polymer and a conductive material, comprising the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic ester and its derivatives, 1.5 parts of an initiator, 12 parts of a conductive agent, 3 parts of a conductive polymer, 8 parts of a functional enhancer, 2.5 parts of an environmentally friendly additive, and 200 parts of deionized water.
[0115] The modified conductive agent is graphene.
[0116] The conductive polymer is polypyrrole.
[0117] The environmentally friendly additive includes 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is carboxymethyl starch; and the biodegradable plasticizer is polyadipate.
[0118] The surfactant is selected from sodium lauryl sulfate.
[0119] Acrylic acid and its salts are methacrylic acid and its salts; acrylic acid esters and their derivatives include methyl acrylate.
[0120] The initiator is potassium persulfate.
[0121] The preparation method is the same as that of Example 1.
[0122] Comparative Experimental Design
[0123] Experiment 1: Conductivity Test
[0124] Purpose: To test the effects of different conductive agents and conductive polymers on the conductive properties of adhesives.
[0125] Method: The conductivity (S / m) of the conductive adhesive was measured using the four-probe method.
[0126]
[0127]
[0128] Analysis of experimental results: The modified conductive agents (modified conductive carbon black, modified carbon nanotubes, modified graphene) used in the examples all significantly improved the conductivity. Compared with the unmodified conductive agent, the conductivity was increased by 87%, 89%, and 106%, respectively. The reason is that the modification process introduced functional groups (such as carboxyl groups, amino groups) or composite conductive polymers (such as pyrrole and aniline), which effectively improved the dispersibility and electronic conductivity of the conductive agent, thereby forming a more stable conductive network. The conductive polymer (polypyrrole or polyaniline) in the examples further enhanced the conductivity. For example, the conductivity of Example 3 (25.6 S / m) was increased by 106% compared with 12.4 S / m of Comparative Example 3 (unmodified graphene, no conductive polymer). The conductive polymer has a good conductivity. It acts as a "bridge" in the electrical network, connecting the dispersed conductive agent particles, increasing the electron conduction path and efficiency; the modified graphene has the best conductivity (25.6S / m), because its two-dimensional layer structure has a larger specific surface area and higher electron mobility, and the surface composite polypyrrole further optimizes the electron transmission path; the modified carbon nanotubes are second (20.3S / m), although its one-dimensional linear structure has excellent conductivity, its dispersibility in aqueous systems is slightly inferior to that of modified graphene; the modified conductive carbon black performs well (15.8S / m), which is 86% higher than the conductivity of unmodified carbon black (8.5S / m), but its conductivity is slightly lower than the other two modified conductive agents due to the limitations of specific surface area and structural stability.
[0129] Conclusion: The modified conductive agent significantly improves the conductivity of the binder, especially the modified graphene + conductive polymer combination performs best. The binder of the embodiment forms a stable and efficient three-dimensional conductive network, which can better meet the demand of lithium-ion batteries for conductive properties.
[0130] Experiment 2: Cyclic stability test
[0131] Purpose: To test the effect of functional enhancers on the bonding strength and cycle stability of binders on electrode materials.
[0132] Method: The binder was coated on the silicon-based negative electrode, and the electrode capacity retention rate was tested after 200 charge and discharge cycles.
[0133]
[0134]
[0135] Analysis of experimental results: The self-healing monomer (urethane acrylate) introduced in the example forms a dynamic hydrogen bond network during the electrode cycle, which can achieve self-repair after cracks are generated, thereby maintaining the structural integrity of the electrode; the capacity retention rate of Example 3 (96.8%) is 21.5 percentage points higher than that of Comparative Example 4 (75.3%), indicating that the self-healing monomer is effective in alleviating electrode expansion and cracking; the thermal responsive monomer (N-isopropylacrylamide) in Example 1 buffers the volume change of the electrode through the thermosensitive swelling effect, preventing bonding failure under extreme conditions, which is relatively Compared with Comparative Example 1 in which no thermal responsive monomer is added, the capacity retention rate is increased from 78.9% to 92.5%, which significantly improves the cycle stability under high temperature environment; the ceramic nanoparticles (such as TiO2) introduced in the embodiment enhance the mechanical strength of the binder, and the interfacial coupling agent (such as silane coupling agent) effectively improves the interfacial bonding force between the binder and the electrode active material; it shows that the addition of the functional enhancer significantly improves the bonding strength and cycle stability of the electrode, and the binder in the embodiment not only has high bonding strength, but also exhibits excellent durability and reliability in high-rate cycles.
[0136] In summary, the present invention uses modified conductive carbon black, modified carbon nanotubes and modified graphene as conductive agents, and combines them with conductive polymers to form a stable three-dimensional conductive network in the binder, thereby significantly improving the conductive properties of the binder. This network structure helps to reduce interface resistance and improve the rate performance and energy density of the battery. In the present invention, by introducing functional enhancers such as self-healing monomers, thermal responsive monomers, ceramic nanoparticles, and interface coupling agents, the binder has higher tensile and crack resistance and can maintain a good bonding effect when the electrode volume changes. At the same time, the self-healing function can extend the service life of the binder, thereby improving the cycle stability of the battery. The present invention adopts Using water as the dispersion medium completely avoids the environmental pollution caused by organic solvents used in traditional binders. In addition, the addition of environmentally friendly additives such as bio-based materials and biodegradable plasticizers further improves the environmental friendliness of the materials and makes the treatment of waste batteries safer. The present invention adopts emulsion polymerization technology, and through multi-step pre-reaction and step-by-step polymerization processes, it ensures the uniform distribution of binder components and the controllability of molecular structure, while reducing energy consumption in the preparation process. The water-based conductive binder can be adapted to a variety of positive and negative electrode materials (such as silicon-based negative electrodes, high-nickel ternary positive electrodes, etc.), meet the needs of different lithium-ion battery application scenarios, and show excellent interface compatibility and adhesion properties.
[0137] Finally, it should be noted that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A water-based conductive adhesive for lithium-ion batteries, characterized in that: The conductive adhesive is an in-situ reaction complex of an emulsion polymer and a conductive material, and comprises the following components in parts by weight: 1 to 10 parts of a surfactant, 5 to 40 parts of acrylic acid and its salts, 5 to 40 parts of acrylic esters and their derivatives, 0.1 to 2 parts of an initiator, 1 to 15 parts of a modified conductive agent, 0.5 to 5 parts of a conductive polymer, 2 to 15 parts of a functional enhancer, 1 to 5 parts of an environmentally friendly additive, and 50 to 200 parts of deionized water.
2. The aqueous conductive binder for lithium-ion batteries according to claim 1, characterized in that: The conductive adhesive is an in-situ reaction complex of an emulsion polymer and a conductive material, and comprises the following components in parts by weight: 10 parts of a surfactant, 15 parts of acrylic acid and its salts, 10 parts of acrylic esters and their derivatives, 1.5 parts of an initiator, 12 parts of a modified conductive agent, 3 parts of a conductive polymer, 8 parts of a functional enhancer, 2.5 parts of an environmentally friendly additive, and 200 parts of deionized water.
3. The aqueous conductive binder for lithium-ion batteries according to claim 1, characterized in that: The modified conductive agent is any one of modified conductive carbon black, modified carbon nanotubes, and modified graphene, and the modification steps are respectively as follows; Modified conductive carbon black: suspend the conductive carbon black in water, add nitric acid / sulfuric acid mixed acid with a volume ratio of 1:3, disperse by ultrasonic for 1 hour, and stir at 80°C for 4 hours; Modified carbon nanotubes: disperse carbon nanotubes in nitric acid solution, stir and react at 80°C for 5 hours to introduce carboxyl functional groups, then react with ammonia water to generate amino carbon nanotubes, and finally graft polymerize with acrylic monomers through amino groups; Modified graphene: Graphene oxide is used as a precursor, and a hydrothermal method is used to reduce and generate partially reduced graphene oxide. Pyrrole or aniline monomers are modified on the surface of graphene oxide, and a conductive polymer composite is formed through in-situ chemical oxidation polymerization.
4. The aqueous conductive binder for lithium-ion batteries according to claim 1, characterized in that: The conductive polymer is any one of polypyrrole or polyaniline.
5. The aqueous conductive binder for lithium-ion batteries according to claim 1, characterized in that: The functional enhancer includes 2 parts of self-healing monomer, 2 parts of thermal response monomer, 1 part of ceramic nanoparticles, and 3 parts of interface coupling agent; wherein the self-healing polymer is urethane acrylate; the thermal response monomer is N-isopropyl acrylamide; the ceramic nanoparticles are any one of TiO2, Al2O3, and SiO2; and the interface coupling agent is any one of silane coupling agent and titanate coupling agent.
6. The aqueous conductive binder for lithium-ion batteries according to claim 1, characterized in that: The environmental protection additive comprises 1 part of bio-based material and 1.5 parts of biodegradable plasticizer; the bio-based material is any one of carboxymethyl starch, carboxymethyl cellulose and hydroxypropyl cellulose; the biodegradable plasticizer is polyadipate.
7. The aqueous conductive binder for lithium-ion batteries according to claim 1, characterized in that: The surfactant is selected from any one or more of the following combinations: sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium pyrophosphate, polyethylene glycol ether, polypropylene glycol ether, ethylene oxide-propylene oxide block copolymer, polyvinyl alcohol, polysorbate, and sorbitan fatty acid ester.
8. The aqueous conductive adhesive for lithium-ion batteries according to claim 1, characterized in that: The acrylic acid and its salts include any one or more combinations of acrylic acid, methacrylic acid and its sodium, potassium, lithium, ammonium salts, itaconic acid and its salts, maleic acid and its salts; the acrylic acid esters and their derivatives include any one or more combinations of methyl acrylate, ethyl acrylate, propyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, polyethylene glycol acrylate, etc.
9. The aqueous conductive binder for lithium-ion batteries according to claim 1, characterized in that: The initiator includes any one or more combinations of potassium persulfate, ammonium persulfate, and azobisisobutyramidine hydrochloride.
10. A method for preparing a water-based conductive binder for lithium-ion batteries according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add a surfactant to deionized water, stir evenly, then add a modified conductive agent, and perform ultrasonic dispersion for 30 to 60 minutes at room temperature to evenly disperse the modified conductive agent in water to obtain a dispersion D; Acrylic acid and its salts and part of acrylic acid esters and their derivatives are sequentially added to the dispersion D, and an initiator is added. After nitrogen is passed through to deoxygenate for 10 to 30 minutes, the system is heated to 60 to 85° C. and stirred at a constant temperature for 1 to 4 hours to form a pre-reactant A. A portion of the pre-reactant A is mixed with the remaining acrylate and its derivatives, and a conductive polymer and a functional enhancer are added, and emulsified and stirred at room temperature for 30 minutes to obtain an emulsified monomer B. Meanwhile, the remaining initiator is dissolved in deionized water to obtain an initiator solution C; The emulsified monomer B and the initiator solution C are slowly added to the remaining pre-reactant A by dropwise addition (2 to 10 hours), and the temperature of the reaction system is maintained at 65 to 85°C. After the dropwise addition is completed, the reaction is carried out at a constant temperature for 2 to 8 hours to ensure that the polymerization is fully completed to form a uniform adhesive matrix; Add environmentally friendly additives to the adhesive matrix, stir evenly, filter and remove impurities, cool to room temperature, and obtain a finished adhesive.
Citation Information
Cited By
High-dispersion solution type negative electrode binder, preparation method and application
CN122278394A